2009
DOI: 10.1007/s00296-009-0915-6
|View full text |Cite
|
Sign up to set email alerts
|

Multi-system mitochondrial disorder with recurrent steroid-responsive eosinophilia

Abstract: Objectives: Though mitochondrial disorders due to a respiratory chain defect may manifest with haematological abnormalities such as anaemia, neutropenia, or thrombocytopenia, recurrent steroid-responsive eosinophilia has not been reported as a manifestation of a mitochondrial disorder.Clinical presentation and intervention: In a polymorbid 65yo female recurrent erythema, asthma, chronic bronchitis, gastritis with eosinophilic granuloma, recurrent episodes hypereosinophilia, and polyarthralgia suggested Churg-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…MID was diagnosed based on the patient's clinical presentation and muscle biopsy findings (single ragged-red fibres, COX-negative fibres and slight increase in glycogen). (34) However, in the present study, eosinophilia attributable to MID was not infrequent; it was found in 11 patients, four of whom also had other haematological abnormalities. Therapeutic options depend on the type of blood cell abnormality.…”
Section: Syndromiccontrasting
confidence: 65%
See 1 more Smart Citation
“…MID was diagnosed based on the patient's clinical presentation and muscle biopsy findings (single ragged-red fibres, COX-negative fibres and slight increase in glycogen). (34) However, in the present study, eosinophilia attributable to MID was not infrequent; it was found in 11 patients, four of whom also had other haematological abnormalities. Therapeutic options depend on the type of blood cell abnormality.…”
Section: Syndromiccontrasting
confidence: 65%
“…Finsterer and Höger reported eosinophilia in a 65-year-old woman (who had pituitary adenoma, basal ganglia calcification, tetraspasticity, restless legs, hypoacusis, tinnitus, atrial fibrillation, myopathy, polyneuropathy, polyarthralgia, osteoporosis, hyponatraemia and hyperlipidaemia), which was attributed to non-syndromic, multisystem MID after a muscle biopsy and exclusion of ChurgStrauss syndrome. (34) She also presented with a history of recurrent thrombopenia in addition to eosinophilia. MID was diagnosed based on the patient's clinical presentation and muscle biopsy findings (single ragged-red fibres, COX-negative fibres and slight increase in glycogen).…”
Section: Syndromicmentioning
confidence: 99%
“…Steroids may be useful in resolving episodic eosinophilia but may be ineffective for other features of mitochondrial disorders. 10 The exact mechanisms of hypereosinophilia-induced encephalopathy remain unclear. MRI in this patient revealed focal lesions mainly in the cortical gray matter, different from those of multiple sclerosis, or diffuse cerebrovascular atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…A possible impact of membrane stabilizing effect has been suggested. There have been anecdotal and hypothetical suggestions of their utility in certain multisystem mitochondrial disorders on the basis of a favorable response to steroids [66]. Recent research has also linked mitochondrial diseases to the etiology of infantile spasms where steroid treatment is a wellknown and successful treatment modality [67].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Ketogenic diet, induction of artificial starvation like state, has been studied in patients with low PDH activity as it is said to bypass the PDC deficiency. Ketogenic diet has been recommended for children with refractory epilepsy due to PDC deficiency [66].…”
Section: Dietmentioning
confidence: 99%